Perancangan Multimedia Interaktif Untuk Kampanye Penghematan Energi Listrik Rumah Tangga - Andi Dahroni; Eka Putra; Muhammad Fadli Pratama (Sekolah Tinggi Teknik - PLN, 2019)
The limited development of power plants in the last five years has an impact on electricity supply in several regions in Indonesia. If you want to continue to feel electricity in Indonesia, one of the things that electricity users in Indonesia must do now is to save electricity. Media and technology can now be used by the government to promote electricity saving. The multimedia design program of the campaign for electronic voting was designed and created which would later be expected to provide simple education for the community in wise electronic selection. Designing interactive multimedia programs using the MDLC design method. The results of this study can foster a sense of community awareness of the electrical energy used to use electricity carefully. It was proven by 86% of respondents saying that the existence of a game of interactive applications in the form of games could make the community think wiser and adaptive